Reversible Cortical Blindness and Internuclear Ophthalmoplegia after Neurosurgical Operation: Case Report and Review of the Literature - Kuhnt, Daniela; Becker, Andreas; Benes, Ludwig; Nimsky, Christopher (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background The reversible posterior leukoencephalopathy (RPL) syndrome with typical vasogenic edema in the occipital lobe and associated cortical blindness is a rare finding; however, the brainstem variant is even more infrequent. Etiologies discussed include blood pressure dysregulations, renal failure, or immunosuppression.Patient A 63-year-old man with the characteristic radiographic findings of RPL syndrome presented with reversible cortical blindness and internuclear ophthalmoplegia (INO) after resection of an infratentorial hemangiopericytoma. The patient postoperatively presented with diplopia and mental status alterations followed by visual loss; these symptoms completely recovered within a few days. Fluid-attenuated inversion recovery-, and T2-weighted magnetic resonance imaging (MRI) revealed bilateral hyperintense lesions not only in the white matter of the parieto-occipital region but also in the rostral paramedian mesencephalon and pons.Conclusions We hypothesize that the patient had an RPL, coincidentally in classic-, and brainstem localization, caused by perioperative fluctuations of blood pressure.
Keywords: reversible posterior leukoencephalopathy (RPL); internuclear ophthalmoplegia (INO); hemangiopericytoma